Comparative Analysis of Islamic Religious Education Teaching Methods and Their Impact on Mathematical Thinking Skills - Ibnu Imam Al Ayyubi; Eko Prayetno; Nurhikmah; Indri Saputri; Akhbar Susilo (International Journal of Education Management and Religion, 2025)
This study aims to analyze the differences in Islamic Religious Education (PAI) learning methods and their impact on students' mathematical thinking skills at SMK Roudlotul ‘Ulum, which operates under the Roudlotul ‘Ulum Islamic Boarding School Foundation in West Bandung. The population of this study includes all students at SMK Roudlotul ‘Ulum, with a sample consisting of two classes: Class X1 with 33 students and Class X2 with 28 students. The study employs a mixed-method approach with an embedded design in a comparative study. The sampling technique used is non-probability sampling with purposive sampling. Data analysis includes both quantitative and qualitative approaches. The findings reveal that the data are not normally distributed and not homogeneous; therefore, the nonparametric Mann-Whitney U-Test was conducted. Statistical analysis indicates a significant difference between the two classes, with a significance value of 0.008 (p<0.05). Interviews with students support these findings, showing that the problem-based learning approach used in Class X2 was more effective in integrating religious values with mathematical thinking skills compared to the lecture-based method used in Class X1. This study highlights the importance of innovation in Islamic Religious Education teaching methods to holistically develop students' logical and critical thinking skills. The practical implications of this research can serve as a guide for educators in designing more contextual and relevant learning methods, as well as for policymakers to encourage the implementation of problem-based learning approaches in schools, particularly in Islamic Religious Education subjects.